Kvizi iz Matematike I: 1. del - Tepeh, Aleksandra (University of Maribor Press, 2023)
Mathematics 1 Quizzes: Part One.The present collection of solved exercises is an educational tool primarily intended for first-year students of the Computer Science and Information Technologies and Informatics and Technologies of Communication study programs at the University of Maribor’s Faculty of Electrical Engineering and Computer Science (UM FERI) who are taking the subject Mathematics 1. Since most natural science and technical study programs at other faculties cover the same material in the first year, it is also intended for a broader audience. The first part of the collection covers topics in basic logic, sets, complex numbers, and functions. It encourages students to prepare good notes, which is one of the foundations for successful exam preparation. The publication is co-financed by the European Union - NextGenerationEU and the Republic of Slovenia, Ministry of Higher Education, Science and Innovation.